ANALYSIS OF CULVERT APPROACHES WITH PILES OF VARYING LENGTH - M. R. Madhav; P. K. Basudhar; N. Miura (Lowland Technology International, 1999)
For the construction of culverts and their approaches on soft and highly compressible soils, an innovative approach is to provide piles with length decreasing with distance from the culvert. The equivalent stiffness of the piled strip as a function of the relative length of the piles estimated from Brown and Wiesner (1976), is bounded by Linear and exponential variations with distance. An extended Pasternak type model is proposed for the culvert approaches with piles of varying length. The response of the system is shown to be governed by the relative stiffnesses of the granular bed, the culvert foundation, the approaches at the near and far ends and the relative pile length to diameter ratio. The settlement profiles are presented for the typical values of the above parameters. The relative stiffness of the granular pad has a significant effect on settlements and on the loads transferred to the culvert foundations.